PENERAPAN BUDIDAYA SAYURAN DAUN MENGGUNAKAN SISTEM VERTIKULTUR DI DUSUN 2 DESA KARANGINDAH - Sofyan, Fakhrizal Agustian; Iva Prestiana, Novita Dian; Qintharah, Yuha Nadhirah (Universitas Islam 45 Bekasi, 2024)
Karangindah is a village located in Bojongmangu Subdistrict, Bekasi Regency, West Java Province, Indonesia. Based on 2022 data, this village has a population of 3,286 people. Most of the residents of Karang Indah Village work as farmers, while others run businesses in various MSME sectors. The implementation methods applied in community service activities in Dusun 2 Karangindah Village include socialization or counseling regarding the potential and utilization of yard land for agricultural production to the local community. The implementation of community service activities is carried out through several stages in the implementation of its activities, namely including (1) socialization related to the potential of yard land that can be utilized by the community in Dusun 2 Karang Indah, (2) providing training on plant cultivation procedures using verticulture pots as a method of vegetable cultivation, (3) monitoring the implementation of work programs that have been implemented in Dusun 2 Karang Indah to see plant growth. Based on the implementation of community service activities in the form of applying vegetable cultivation with a verticulture system in Hamlet 2, this activity ran successfully and smoothly. The cooperation and coordination of the community in Hamlet 2 went well, giving a positive impact, especially on the growth of the plants.